Plastics in life cycle perspective: Insights from the ELCA literature - Malte Johannes Endler; André Wolf (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2019)
The main purpose of this article is to provide an introduction to the methodological approach and current insights of the ELCA literature related to plastic from the point of view of a non-technician. Concerning potential remedies, we set our focus on the question to what extent the use of biomass as an alternative feestock in plastic production can contribute to a reduction of the environmental burden.
Keywords: 330